2019
DOI: 10.1155/2019/5487890
|View full text |Cite
|
Sign up to set email alerts
|

Authenticating Raw from Reconstituted Milk Using Fourier Transform Infrared Spectroscopy and Chemometrics

Abstract: Fourier transform infrared (FTIR) spectroscopy combined with chemometrics was used to authenticate raw milk from their reconstituted counterparts. First, the explanatory principal component analysis (PCA) was employed to visualize the relationship between raw and reconstituted milk samples. However, the degree of separation between two sample classes was not significant according to direct observation of the scores plot, indicating FTIR spectra may contain complicated chemical information. Second, partial leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 21 publications
(26 reference statements)
0
13
0
Order By: Relevance
“…Model overfitting is avoided because it affects the classification performance and gives bias results. An internal and external validation test using 11 latent variables confirmed the validity of the PLS-DA model with the accuracy of 98% [ 12 ].…”
Section: Chemometricsmentioning
confidence: 99%
See 1 more Smart Citation
“…Model overfitting is avoided because it affects the classification performance and gives bias results. An internal and external validation test using 11 latent variables confirmed the validity of the PLS-DA model with the accuracy of 98% [ 12 ].…”
Section: Chemometricsmentioning
confidence: 99%
“…The application of chemometrics or multivariate data analysis (MDA) is emerging in the authentication of milk using FTIR spectroscopy (Irnawati et al, 2021). Several studies have reported using chemometrics for classification of milk such as the authentication of raw milk from reconstituted milk with FTIR spectroscopy combined partial least square-discriminant analysis (PLS-DA) [ 12 ], the detection of formalin in cow milk using ATR-FTIR spectroscopy combined with PCA and its quantification using PLS [ 13 ], and the detection and quantification of urea in milk using FTIR spectroscopy combined with multivariate analysis (PCA and PLS) [ 14 ]. Capuano et al [ 15 ] have reported using FTIR spectra and PLS-DA for classification of milk from cow that were fed with or without fresh grass.…”
Section: Chemometricsmentioning
confidence: 99%
“…PLS-DA model is used to optimize separation between different groups of samples and is completed by linking two matrices: X (the spectral data) and dependent variable (groups, class membership etc.). PLS constructs a linear regression model by projecting the predictor variables and response variables to a new set of latent variables (LVs), called factors, with maximum covariance [23] PLS-DA was performed in the fingerprint region 1800-750 cm −1 . PLS-DA models were extracted at a confidence level of 95%…”
Section: Partial Least Squares-discriminant Analysis (Pls-da)mentioning
confidence: 99%
“…After olive oil, milk is the second food item that is at risk of adulteration [ 67 , 68 , 69 ]. Adulteration of milk can have economic purposes as in the case of the addition of vegetable proteins, milk of different species, addition of whey and water, not representing any serious risk to health.…”
Section: Application Of Ft-mir To Food Analysismentioning
confidence: 99%